2018
DOI: 10.1002/jia2.25032
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian network for HIV Drug Resistance Surveillance (HIV‐BresNet): a survey of treatment‐naive individuals

Abstract: IntroductionIn Brazil, more than 487,450 individuals are currently undergoing antiretroviral treatment. In order to monitor the transmission of drug‐resistant strains and HIV subtype distribution in the country, this work aimed to estimate its prevalence and to characterize the nationwide pretreatment drug resistance in individuals recently diagnosed with HIV between 2013 and 2015.MethodsThe HIV threshold survey methodology (HIV‐THS, WHO) targeting antiretroviral‐naive individuals with recent HIV diagnosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
53
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 31 publications
12
53
3
2
Order By: Relevance
“…However, these results differed from those of Sprinz et al and Murillo et al, who found a higher frequency of TDRMs for NNRTIs [11] and from other studies that found a higher frequency of TDRMs for NRTIs, then for NNRTIs and for PIs [13, 34]. The K103N TDRM was the most frequently found in this study and has been described in other studies conducted in different regions of Brazil [13, 3335, 38]. The presence of this mutation is associated with high levels of resistance to NNRTI Nevirapine and Efavirens, which were part of the recommended regimen for initial therapy in HIV-1 infections at the time of sample collection.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…However, these results differed from those of Sprinz et al and Murillo et al, who found a higher frequency of TDRMs for NNRTIs [11] and from other studies that found a higher frequency of TDRMs for NRTIs, then for NNRTIs and for PIs [13, 34]. The K103N TDRM was the most frequently found in this study and has been described in other studies conducted in different regions of Brazil [13, 3335, 38]. The presence of this mutation is associated with high levels of resistance to NNRTI Nevirapine and Efavirens, which were part of the recommended regimen for initial therapy in HIV-1 infections at the time of sample collection.…”
Section: Discussioncontrasting
confidence: 98%
“…The prevalence of TDRMs found in different studies varies according to the region and the population studied [2731]. Based on the WHO HIVDR classification [32], the present study demonstrated a moderate level of resistance, which is in accordance to a recent survey conducted by Arruda et al that revealed moderate rate of TDRM in the five Brazilian macroregions [33]. Sax et al reported that in places where the prevalence of transmitted resistance is 1% or higher, testing for resistance before starting ART is considered cost-effective [5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In Manaus, 21.4% TDR was recently described among 117 newly diagnosed ARV‐naive children, in which 28.8% was previously exposed to mother‐to‐child ARV prophylaxis . A recent nationwide study with 1,558 patients showed 9.5% TDR and the 10.2% rate reported in the Northern region is similar to our findings . In 128 ARV‐naive, chronically infected blood donors (from Sao Paulo, Minas Gerais, Pernambuco, and Rio de Janeiro states), a high prevalence of TDR was detected in near full‐length HIV‐1 genomes obtained by ultradeep sequencing, which increases the detection of DRM .…”
Section: Discussionsupporting
confidence: 89%
“…In the case of dolutegravir, the concern about possible neural tube defects would not be relevant in these populations . The risk of NRTI mutations remains low, even in comparison to Brazil , which recently reported a similar estimate for overall TDR but a threefold higher proportional risk for NRTI DRM. Our data therefore show little threat to the efficacy of NRTIs in current use in ART or as PrEP.…”
Section: Discussionmentioning
confidence: 99%